Adjustments in the Eurozone: Varieties of Capitalism and the Crisis in Southern Europe - Anke Hassel (London School of Economics and Political Science (LSE), European Institute, 2014)
This paper investigates the causes of, and reactions to, the Eurozone crisis, focusing in particular on the institutional foundations of the four Southern European Eurozone countries that have encountered an acute sovereign debt crisis. Applying the basic arguments featured in the Varieties of Capitalism literature, the paper aims to show how the interaction of the institutional set-up of coordinated and mixed market economies, with the effects of the common currency area, can explain both the evolution of the crisis, as well as the reactions to it. This paper interprets the sovereign debt crisis in the Eurozone as the combination of two features: firstly, the architecture of the common currency area, which instituted a common interest rate for widely heterogeneous regional economies, and secondly, the specific institutional foundations of two types of economies participating in the Eurozone, namely coordinated market economies and mixed market economies. Understanding these two factors and their interaction not only helps to explain why the Southern European countries were particularly vulnerable to exploding public debt, but also why, during the on-going resolution of the Eurozone crisis over the last two years, policy makers have persistently preferred austerity over the mutualisation of debt. The compensatory role of the state in mixed-market economies thereby undermines the effectiveness of financial bail-outs for economic growth strategies.
Keywords: 330; comparative political economy; Varieties of Capitalism; European Monetary Union; institutional analysis